Design and Development of a Test Method for Analyzing Protective Performance of Gloves Exposed to Radiant Heat Based on Computational Fluid Dynamics Analysis. Issue 1 (20th January 2019) - Udayraj,; Talukdar, Prabal; Das, Apurba; Alagirusamy, Ramasamy
ABSTRACT: Gloves are one of the most important items in the protective ensemble as they protect hand which is the most frequently burned body part. At present, no international standard or standardized test method is available for analyzing thermal protective performance of gloves exposed to purely radiant heat exposures. In the present work, a systematic approach for developing test setup for radiant heat exposure is proposed using computational fluid dynamics (CFD). A coupled CFD–radiation heat transfer model is first developed and validated with available experimental data. Effects of horizontal and vertical orientations of radiant heaters are then analyzed. Based on this study, an optimized configuration of the experimental setup which results in uniform heat flux distribution throughout the hand under lower level of radiant heat exposure is proposed. Furthermore, effects of different heater temperatures on heat flux distribution are studied. It is found that the proposed configuration works satisfactorily for other higher and lower heat flux levels as well.